Security and privacy in network namespaces - Ferreira, Rui Abreu de Carvalho (2020)
Security and Privacy are now at the forefront of modern concerns, and drive a significant part of the debate on digital society. One particular aspect that holds significant bearing in these two topics is the naming of resources in the network, because it directly impacts how networks work, but also affects how security mechanisms are implemented and what are the privacy implications of metadata disclosure. This issue is further exacerbated by interoperability mechanisms that imply this information is increasingly available regardless of the intended scope. This work focuses on the implications of naming with regards to security and privacy in namespaces used in network protocols. In particular on the imple- mentation of solutions that provide additional security through naming policies or increase privacy. To achieve this, different techniques are used to either embed security information in existing namespaces or to minimise privacy ex- posure. The former allows bootstraping secure transport protocols on top of insecure discovery protocols, while the later introduces privacy policies as part of name assignment and resolution. The main vehicle for implementation of these solutions are general purpose protocols and services, however there is a strong parallel with ongoing re- search topics that leverage name resolution systems for interoperability such as the Internet of Things (IoT) and Information Centric Networks (ICN), where these approaches are also applicable.